Capacity of Bicycle Platoon Flow at Two-Phase Signalized Intersection: a Case Analysis of Xi’an City - Wang, Yong-Gang; Wei, Gang; Zhu, Xu; Pei, Yu-Long (Promet - Traffic&Transportation, 2011)
Although much is known about the operation of signalized intersections, little or no empirical research has been conducted regarding bicycle capacity at these locations and the correspondent contributory factors. The purpose of this study is to accurately quantify the capacity of bikeway at signalized intersection through a fluid dispersion approach, and ultimately the lane group capacity. Using this total dispersion of bicycle flow, a relationship is also described between bicycle volume per hour and per unit width, signal parameters (length of signal cycle and green time), bicycle flow (arrival rate, density, moving velocity) and geometric intersection distance. Through the videotaping of four intersections that have significant bicycle traffic around Xiaozhai in Xi’an, China, it is ascertained that bicycle capacity varies linearly (but limited by an asymptote domain) associated with the adjustment of these parameters. The analytical results indicate that the impact saturation flow of lane groups containing right-turning vehicles and pedestrian flow at signalized intersections on bicycles is being underestimated. If this is the case, then capacity is being overestimated through the HCM 2000 capacity model and JJ37-90 approach and intersections are not being adequately designed, due to the neglect of conflict nature of mixed traffic arrivals in competing for space.